2012
DOI: 10.1371/journal.pone.0044431
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Disease Prediction and Modeling through the Use of Meteorological Ensembles: Human Plague in Uganda

Abstract: Climate and weather influence the occurrence, distribution, and incidence of infectious diseases, particularly those caused by vector-borne or zoonotic pathogens. Thus, models based on meteorological data have helped predict when and where human cases are most likely to occur. Such knowledge aids in targeting limited prevention and control resources and may ultimately reduce the burden of diseases. Paradoxically, localities where such models could yield the greatest benefits, such as tropical regions where mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 65 publications
0
50
0
Order By: Relevance
“…Lower elevation sites are typically warmer and drier and have sandier soils than sites above the escarpment. 11,13,16 Previous studies showed that human plague cases are more common above the escarpment than below. 11,14 Correspondingly, flea species diversity is significantly higher above the escarpment within the plague focus, compared with lower elevation sites outside the focus, and this has been hypothesized to be important for enzootic maintenance of Y. pestis.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lower elevation sites are typically warmer and drier and have sandier soils than sites above the escarpment. 11,13,16 Previous studies showed that human plague cases are more common above the escarpment than below. 11,14 Correspondingly, flea species diversity is significantly higher above the escarpment within the plague focus, compared with lower elevation sites outside the focus, and this has been hypothesized to be important for enzootic maintenance of Y. pestis.…”
Section: Methodsmentioning
confidence: 99%
“…13 Modeling of inter-annual variation showed that annual plague case counts were negatively associated with dry season rainfall (December-February) and positively associated with rainfall immediately preceding the plague season. 13 Spatial risk modeling has demonstrated that in the West Nile Region, plague risk is higher above 1,300 meters above sea level than below this value. Furthermore, covariates included in these models suggested that localities that are generally wetter, but with discontinuous rainfall, pose an increased risk for plague compared with drier areas.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations